2016
DOI: 10.1080/02619768.2016.1246528
|View full text |Cite
|
Sign up to set email alerts
|

The professional developmental needs of higher education-based teacher educators: an international comparative needs analysis

Abstract: A universal lack of attention to the professional learning needs of teacher educators is the driver for this study, which considers the most effective ways to support the professional learning of higher education-based teacher educators. At a time when many industrialised countries are engaged in systemic educational reform, this study provides an international and comparative needs analysis through a survey of 1,158 higher education-based teacher educators in the countries participating in the International F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
108
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 26 publications
3
108
1
6
Order By: Relevance
“…A certain ambivalence appeared towards the type of research teacher educators should conduct. The prior survey revealed that practitioner research was one of the prioritised learning needs (Czerniawski et al 2017). While the interviews did not highlight this, practitioner research can still be considered as a way to combine research and teaching that might add to both (Cochran-Smith 2005).…”
Section: The Induction Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…A certain ambivalence appeared towards the type of research teacher educators should conduct. The prior survey revealed that practitioner research was one of the prioritised learning needs (Czerniawski et al 2017). While the interviews did not highlight this, practitioner research can still be considered as a way to combine research and teaching that might add to both (Cochran-Smith 2005).…”
Section: The Induction Periodmentioning
confidence: 99%
“…As a result, there has been a growing interest in teacher educators: their identity, skills, roles and professional development (Loughran 2014, Lunenberg et al 2014. While teacher educators can be defined as those who are involved in the education of student teachers as well as continued professional development of in-service teachers (European Commission, 2013, Czerniawski et al 2017, the current paper deals with teacher educators who work in higher education institutes (as distinct from teacher educators based in schools). Current literature suggests that while teacher educators perform a multitude of complex roles, they receive minimal preparation or possibilities for professional development to fulfil these roles.…”
Section: Introductionmentioning
confidence: 99%
“…Referring to a Pan-European study of 1158 teacher educators, Czerniawski, Guberman, and MacPhail (2017) found indications that there is a strong desire by teacher educators to be exposed to alternative ways of educating teachers, to learn about national and international developments in teacher education policy and to contribute to teacher education research literature. Thus, and in line with recent research, 'teacher educators' personal goals and commitments are 'central to any conceptualisation of teacher educator professionalism (and development)', (Vanassche and Kelchtermans 2016, 366).…”
Section: Teacher Educators In International Contextsmentioning
confidence: 99%
“…As I stressed in my first editorial (Flores 2017) much has been written on teacher education, but less is known about the identity, working contexts and professional learning of teacher educators, despite the growing interest about the topic in the last years. The need to better understand who teacher educators are and what they do, how they understand their roles and their professional development but also how they see themselves as teacher educators has been widely advocated (see, for instance, Izadinia 2014;Livingston 2014;Flores 2016;Czerniawski, MacPhail, and Guberman 2017). Teacher educators' identity, their professional learning needs throughout their careers and their working contexts have been seen as key elements that deserve further attention in order to overcome the idea of teacher educators as hidden or unrecognised professionals (Livingston 2014) and to shed light on the invisibility of their work (Flores 2016).…”
Section: Tensions and Possibilities In Teacher Educators' Roles And Pmentioning
confidence: 99%